Androgen receptor signaling and mutations in prostate cancer - Koochekpour, Shahriar (Nature Publishing Group, 2010)
Normal and neoplastic growth of the prostate gland are dependent on androgen receptor (AR) expression and function. Androgenic activation of the AR, in association with its coregulatory factors, is the classical pathway that leads to transcriptional activity of AR target genes. Alternatively, cytoplasmic signaling crosstalk of AR by growth factors, neurotrophic peptides, cytokines or nonandrogenic hormones may have important roles in prostate carcinogenesis and in metastatic or androgen-independent (AI) progression of the disease. In addition, cross-modulation by various nuclear transcription factors acting through basal transcriptional machinery could positively or negatively affect the AR or AR target genes expression and activity. Androgen ablation leads to an initial favorable response in a significant number of patients; however, almost invariably patients relapse with an aggressive form of the disease known as castration-resistant or hormone-refractory prostate cancer (PCa). Understanding critical molecular events that lead PCa cells to resist androgen-deprivation therapy is essential in developing successful treatments for hormone-refractory disease. In a significant number of hormone-refractory patients, the AR is overexpressed, mutated or genomically amplified. These genetic alterations maintain an active presence for a highly sensitive AR, which is responsive to androgens, antiandrogens or nonandrogenic hormones and collectively confer a selective growth advantage to PCa cells. This review provides a brief synopsis of the AR structure, AR coregulators, posttranslational modifications of AR, duality of AR function in prostate epithelial and stromal cells, AR-dependent signaling, genetic changes in the form of somatic and germline mutations and their known functional significance in PCa cells and tissues.